An analysis of missed injuries in patients with severe trauma - EunGyu Ju; Sun Young Baek; Sung Soo Hong; Younghwan Kim; Seok Hwa Youn (Journal of Trauma and Injury)
Purpose To analyze the data of trauma patients with undetected injuries at the time of initial resuscitation during the primary and secondary surveys. Methods We retrospectively reviewed the medical records of 807 patients who were hospitalized at the National Trauma Center, Seoul, Korea from June 1, 2019 to June 30, 2021. Results In trauma patients with an Injury Severity Score ≥16 accounted for 27.5% in the non-missed injury group (non-MIG), but this rate was considerably higher at 71.2% in MIG. The mean hospitalization longer in MIG (50.90±39.56) than in non-MIG (24.74±26.11). The proportion of patients with missed injuries detected through tertiary trauma survey (TTS) was 28 patients (23.5%) within 24 hours, 90 patients (75.6%) after 24 hours to before discharge. The majority of missed injuries were fractures (82.4%) and ligament tears (8.4%), which required consultation with the orthopedic department. The final diagnoses of missed injuries were confirmed by computed tomography (44.5%), magnetic resonance imaging (19.3%), X-ray (19.3%), bone scan (11.8%), and physical examination (5.0%). Conclusions TTS is considered a useful process for detecting missed injuries that were not identified at the time of initial resuscitation in the primary and secondary surveys. In the future, to detect missed injuries quickly, it is necessary to develop a suitable TTS program for each trauma center. In addition, further research is needed to verify the effectiveness of the protocolized TTS and survey chart to improve the effectiveness of TTS.